Outpatient Antipsychotic Treatment and Inpatient Costs of Schizophrenia - Marcus, Steven C. (Oxford University Press, 2008)
Objective: To estimate the proportions of acute care inpatient admissions and hospital days for schizophrenia patients in the Medicaid program that are attributable to gaps in outpatient antipsychotic treatment and to calculate the corresponding total health care costs of this care. Methods: A series of multivariate regressions were performed with statewide 2001–2003 California Medicaid data to estimate the fraction of acute care hospital admissions and hospital days for schizophrenia attributable to gaps in antipsychotic medication treatment. This fraction was then applied to national estimates of the number and costs of inpatient treatment episodes for patients with schizophrenia in the national Medicaid program. Results: In the United States, there are roughly 87 000 annual acute care inpatient admissions of Medicaid patients for the treatment of schizophrenia. These admissions include a total of approximately 930 000 hospital days at a total cost of $806 million. Improving adherence to eliminate gaps in antipsychotic medication treatment could lower the number of acute care admissions by approximately 12.3% (95% confidence interval [CI]: 11.7%–12.6%) and reduce the number of inpatient treatment days by approximately 13.1% (CI: 9.8%–16.5%) resulting in a savings of approximately $106 million (95% CI: $79.0 million–$133.0 million) in inpatient care costs for the national Medicaid system. Conclusions: Nonadherence to antipsychotic medication treatment accounts for a considerable proportion of inpatient treatment costs of Medicaid patients with schizophrenia. Improving continuity of antipsychotic medications could lead to savings by reducing the frequency and duration of inpatient treatment.